Cover page. (8th February 2022) - Astorga Roine, Anna; Reid, Brian; Uribe, Luis; Moreno‐Meynard, Paulo; Fierro, Pablo; Madriz, Isaí; Death, Russell G.
Abstract : The cover image is based on the Original Article Macroinvertebrate community composition and richness along extreme gradients: the role of local, catchment and climatic variables in Patagonian headwater streams, by Anna Astorga Roine et al . https://doi.org/10.1111/fwb.13853 .